Living Without Mathematical Statistics Accurate Analysis, Diagnosis, and Prognosis Based on the Taguchi Method - Ruefer, Herbert (Springer International Publishing : Imprint: Springer, 2019)
The book provides structured access to gaining accurate results of limited data applicable to science, technology, and manufacturing. The Taguchi Method is presented in every detail and also put into practice. The basic principle was developed in the 1950's. Dr. Genichi Taguchi (1924 to 2012) kept perfecting his method until 2006, and it has been brought up-to-date until now. The main purpose of this book is to make the above knowledge available to a wide range of people of different backgrounds, regardless of their fields of expertise. .